P-135 FIRST EXPERIENCE WITH A NEW CLOSED INCISION NEGATIVE PRESSURE WOUND THERAPY, PREVENA™, IN ABDOMINAL WALL RECONSTRUCTION PATIENTS. (13th October 2022) - Dixon, S; Benson, A; Kalaiselvan, R; Kanwar, S; Samad, A; Pritchard-Jones, R; West, C; Scott, M
Abstract: Aim: Surgical site infection (SSI) contributes a significant proportion of post operative morbidity in patients undergoing abdominal wall reconstruction (AWR). Prevena™ closed incision negative pressure wound therapy (ciNPT) has been demonstrated to reduce SSI rates in the elective and emergency laparotomy setting. However, there is no evidence for Prevena™ use in AWR patients. The aim of this study was to assess the safety and feasibility of Prevena™ in AWR patients. Materials and Method: Patients undergoing AWR at a single trust were selected at random to receive Prevena™. This was applied to the incision under sterile conditions, a continuous pressure of -125mmHg was applied for 7 days. The primary outcome measure was SSI, with secondary outcomes of 90 day mortality, complications and length of stay. Results: 10 patients received ciNPT in the study period, 8 female 2 male, mean BMI was 34.5. All patients had a Rives-Stoppa repair, with 2 patients also requiring bilateral transversus abdominal release (TAR). A vertical panniculectomy with umboplasty was used in 7 cases, fleur-de-lys panniculectomy with umboplasty in 2 cases, and a single case approached via transverse panniculectomy. There were no deaths within 90 days, median length of stay was 4 days. There was a single SSI managed with oral antibiotics, not requiring admission. Conclusion: Prevena™ has been shown to reduce SSI rates in other patient cohorts and this small series demonstrates it is feasible and safe to use in the AWR setting. Larger studies are required to demonstrate SSI rate reduction in AWR patients.